ANALISIS PENGARUH BEBAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI PT. INDOROTI PRIMA CEMERLANG CABANG BALI - Putri, Ni Luh Made Dwi Meliyanti; Suryawan Wiranatha, A.A.P.A; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 3 (2022): September, 2022)
The increasingly fierce industrial competition in the current era of globalization requires companies to improve employee performance in order to achieve optimal goals. PT Indoroti Prima Cemerlang is one of the industries engaged in food production, namely bread with a well-known brand, namely Mr. Bread. The problems that occur in PT. Indoroti Prima Cemerlang is the instability of employee productivity from month to month. The purpose of this study is to determine the effect of workload and job satisfaction at PT. Indoroti Prima Cemerlang. The method used in this study is the method of factor analysis with the results obtained, namely formed 3 factors that affect employee performance. The second method is the T test and F test with the results of workload having a negative but not significant effect, while job satisfaction has a positive and significant effect on employee performance. The third method is Full Time Equivalent with the results of workload calculations with the FTE index showing that work element I has an FTE index of 1.13. The index shows that the workload on element I is normal because it is in the range between 1-1.28. The work element II has an FTE index of 0.14 which indicates that the workload is classified as underload with a range of FTE values between 0-0.99. Work elements III and IV are classified as overload because they are in the FTE range >1.28.